2023
DOI: 10.1021/acsami.3c00478
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Cationic Eu3+-Metallopolymer with High Quantum Yield and Sensitivity for Intracellular Temperature Sensing

Abstract: Lanthanide-based (Ln3+) luminescent materials are ideal candidates for use in fluorescence intracellular temperature sensing. However, it remains a great challenge to obtain a Ln3+-ratiometric fluorescence thermometer with high sensitivity and quantum yield in an aqueous environment. Herein, a cationic Eu3+-metallopolymer was synthesized via the coordination of Eu(TTA)3·2H2O with an AIE active amphipathic polymer backbone that contains APTMA ((3-acrylamidopropyl) trimethylammonium) and NIPAM (N-isopropylacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Thus, the luminescence intensity ratio (LIR) was selected to achieve ratiometric temperature sensing. LIR thermometry was obtained with the relationship between ln(LIR) values and temperature with eqn (6): 45–47 where A is constant, B is the slope, and T is the absolute temperature. The linear fitting results showed that A is −8.111 and B is 0.034 with a correlation coefficient R 2 of 0.995, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the luminescence intensity ratio (LIR) was selected to achieve ratiometric temperature sensing. LIR thermometry was obtained with the relationship between ln(LIR) values and temperature with eqn (6): 45–47 where A is constant, B is the slope, and T is the absolute temperature. The linear fitting results showed that A is −8.111 and B is 0.034 with a correlation coefficient R 2 of 0.995, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the luminescence intensity ratio (LIR) was selected to achieve ratiometric temperature sensing. LIR thermometry was obtained with the relationship between ln(LIR) values and temperature with eqn (6): [45][46][47] lnðLIRÞ ¼ ln…”
Section: Ratiometric Temperature Sensingmentioning
confidence: 99%
“…Materials with Er-doping have become the main choice for optical temperature sensing by FIR technology, which benefits from the transition luminescence corresponding to the thermal coupling levels 2 H 11/2 and 4 S 3/2 of Er 3+ , and high intensity of a green thermal fluorescence signal captured easily by detection. Here, based on the FIR analysis, the best sample of BOB-E 0.25 Y 0.25 MFs is excited at 977 nm. The spectra of UC luminescence in the temperature range from 303 to 433 K with an interval of 10 K are shown in Figure a,b.…”
Section: Resultsmentioning
confidence: 99%
“…Poly­( N -isopropylacrylamide) ( PNIPAM ) has attracted wide attention due to its extremely temperature-sensitive conformation, clear temperature response mechanism, and adjustable LCST close to human body temperature and is often used to design thermosensitive AIEgen-grafted polymers. Tang et al synthesized PNIPAM-TPE copolymers (Probe 13) by grafting the AIE fluorophore TPE to PINPAM and precisely adjusted the LCST by changing the content of TPE. , The copolymers doped with 0.1% to 2% TPE emit weakly in good solvents at low temperature , but agglomerate and shrink under the thermal stimulation, thus emitting strong fluorescence due to the restricted intramolecular motion (Figure A). In another example, a polymer thermometer of P­(NIPAM- co -EM) (Probe 14) was constructed by grafting the quinoline-malononitrile ( QM ) derivative into the side chain of PINPAM …”
Section: Polymer-based Temperature Sensorsmentioning
confidence: 99%